1985
DOI: 10.1172/jci111759
|View full text |Cite
|
Sign up to set email alerts
|

Renal mechanism of action of rat atrial natriuretic factor.

Abstract: There has been conflict as to whether crude extracts of atrial natriuretic factor increase renal solute excretion by a hemodynamic mechanism or by direct inhibition of tubular transport. To investigate this issue, seven rats were studied during a euvolemic control period and following continuous administration of pure, synthetic 24 amino acid atrial natriuretic factor. A 10-25-fold increase in urinary sodium and chloride excretion occurred with a brisk kaliuresis but little bicarbonaturia. Atrial natriuretic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
86
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(97 citation statements)
references
References 24 publications
10
86
1
Order By: Relevance
“…In previous reports in which atrial natriuretic peptides or atrial natriuretic factors were infused into the renal artery or intravenously to anesthetized animals, a significant increase in GFR was observed during infusion of the peptides Beasley and Malvin 1985;Huang et al 1985). It is not clear why intravenous infusion of ANP failed to increase GFR significantly in the present experiment, but ANP used in the present study was a small dose.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In previous reports in which atrial natriuretic peptides or atrial natriuretic factors were infused into the renal artery or intravenously to anesthetized animals, a significant increase in GFR was observed during infusion of the peptides Beasley and Malvin 1985;Huang et al 1985). It is not clear why intravenous infusion of ANP failed to increase GFR significantly in the present experiment, but ANP used in the present study was a small dose.…”
Section: Discussioncontrasting
confidence: 52%
“…But the mechanism by which atrial extract or atrial natriuretic peptide produces a natriuresis and diuresis is still unclear. Some studies have suggested that contribution of an increase in renal blood flow (Keeler and Azzarolo 1983;Wakitani et al 1985) or glomerular filtration rate Maack et al 1984 ; Beasley and Malvin 1985;Huang et al 1985) to the natriuresis and diuresis, and others have indicated direct tubular effects (Briggs et al 1982; Sonnenberg et al 1982; Pollock and Banks 1983; Burnett et al 1984Burnett et al , 1986Hammond et al 1985).…”
mentioning
confidence: 99%
“…Yet, due to the marked rise in GFR, absolute sodium reabsorption may have been increased, in conformity with animal studies. 27 The main feature of this study is that the natriuretic effect of ANF was attenuated during enalapril treatment. In addition, the rise in GFR, solute free water clearance, phosphate, uric acid, and magnesium excretion and the fall in lithium reabsorption were blunted and nonsignificant.…”
Section: Discussionmentioning
confidence: 84%
“…27 ' 32 This would leave unexplained the increased excretion after administration of ANF of lithium, phosphate, and uric acid, alleged indicators of proximal tubular sodium reabsorption. 16 …”
mentioning
confidence: 99%
“…However, the filtration fraction rose progressively by up to 30%, as noted^jreviously in normal subjects, 4 hypertensive patients, 27 and experimental animals. 37 When possible humoral mediators were considered, plasma renin and aldosterone levels were largely unchanged during human ANF-(99-126) infusion, but they rose (p < 0.05-0.01) during the recovery phase in the renal patients. The latter reaction probably reflects overshoot following a human ANF-(99-126)-induced inhibition of renin secretion and adrenocortical function.…”
Section: Anf In Renal Disease/suda Et Almentioning
confidence: 93%